2021
DOI: 10.1155/2021/8020240
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity Assessment and Protective Effect of Anogeissus leiocarpus Roots against Cyclophosphamide-Induced DNA Damage In Vivo

Abstract: Background. Belonging to the family of Combretaceae, the roots of Anogeissus leiocarpus are traditionally used to treat diabetes, wounds, infections, pain, and gastrointestinal diseases. To our knowledge, no genotoxicity assessment of the plant was reported. Hence, this study was designed to evaluate the potential genotoxic and protective effects of extract of Anogeissus leiocarpus roots using the micronucleus test on mice bone marrow cells in vivo. Methods. Three different concentrations (250, 500, and 1000 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Data in table [1] showed that, CP lead to a significant reduction in the RBCs count after 3 weeks. This reduction attributed to CP toxicity and antimitotic effects on bone marrow cells.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Data in table [1] showed that, CP lead to a significant reduction in the RBCs count after 3 weeks. This reduction attributed to CP toxicity and antimitotic effects on bone marrow cells.…”
Section: Resultsmentioning
confidence: 94%
“…Table [1]: The protective effect of Zn Cl against Cyclophosphamide on peripheral blood cells at the end of study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When AMS35BB is associated with CYC , there is a tendency to potentiate the genotoxic effects of the chemotherapeutic drug. , This can be confirmed by the frequency of cell death in the liver and kidneys. Although the potentiation of micronuclei did not appear significant, the extent of damage increased significantly.…”
Section: Discussionmentioning
confidence: 90%
“…The micronucleus test was conducted according to the OECD 474 guideline 20 . Mice were divided into five groups of five animals.…”
Section: Genotoxicity Evaluation By the Micronucleus Testmentioning
confidence: 99%